An update on physical health and economic consequences of overweight and obesity. Issue 6 (November 2018) - Chu, Dinh-Toi; Minh Nguyet, Nguyen Thi; Dinh, Thien Chu; Thai Lien, Nguyen Vu; Nguyen, Khanh-Hoang; Nhu Ngoc, Vo Truong; Tao, Yang; Son, Le Hoang; Le, Duc-Hau; Nga, Vu Bich; Jurgoński, Adam; Tran, Quoc-Hung; et al.
Abstract: Overweight and obesity (OW and OB) have been on the increase globally and posed health risks to the world's population of all ages, including pre-born babies, children, adolescents, adults and elderly people, via their comorbid conditions. Excellent examples of comorbidities associated with obesity include cancer, cardiovascular diseases (CVD) and type 2 diabetes mellitus (T2DM). In this article, we aimed to review and update scientific evidence regarding the relationships between obesity and its common physical health consequences, including CVD, T2DM, hypertension, ischemic stroke, cancer, dyslipidemia and reproductive disorders. In addition, the economic burden of OW and OB will be discussed. Abundant evidence is found to support the associations between obesity and other diseases. In general, the odd ratios, risk ratios or hazard ratios are often higher in OW and OB people than in the normal-weight ones. However, the molecular mechanism of how OW and OB induce the development of other diseases has not been fully understood. Figures also showed that obesity and its-related disorders exert enormous pressure on the economy which is projected to increase. This review highlights the fact that obesity can lead to numerous lethal health problems; therefore, it requires a lot of economic resources to fight against this epidemic.